An asymmetric chitosan scaffold for tendon tissue engineering: In vitro and in vivo evaluation with rat tendon stem/progenitor cells. (June 2018) - Chen, Erman; Yang, Ling; Ye, Chenyi; Zhang, Wei; Ran, Jisheng; Xue, Deting; Wang, Zhengke; Pan, Zhijun; Hu, Qiaoling
Graphical abstract: Abstract: The poor healing capacity and typically incomplete regeneration of injured tendons has made tendon repair as a primary clinical concern. Several methods for repairing injured tendons have been developed in the last decade. Tendon regeneration using current tissue engineering techniques requires advanced biomaterials to satisfy both microstructural and mechanical criteria. In this study, a novel chitosan (CS)-based scaffold with asymmetric structure was fabricated using a self-deposition technique. The fabricated scaffolds were assessed with regard to the microstructural and mechanical demands of cell ingrowth and the prevention of peritendinous adhesion. In vitro studies showed that rat tendon stem/progenitor cells (TSPCs) seeded onto the CS scaffold displayed higher levels of tenogenic specific genes expression and protein production. Four and six weeks after the implantation of CS scaffolds on full-site Achilles tendon defects, in vivo tendon repair was evaluated by histology, immunohistochemistry, immunofluorescence, and mechanical measurements. The production of collagen I (COL1) and collagen III (COL3) demonstrated that the CS scaffolds were capable of inducing conspicuous tenogenic differentiation, higher tenomodulin (TNMD) production, and superior phenotypic maturity, compared with the empty defect group. The introduction of TSPCs into the CS scaffold resulted in a synergistic effect on tendon regeneration and yielded better-aligned collagen fibers with elongated, spindle-shaped cells. These findings indicated that the application of TSPC-seeded CS scaffolds would be a feasible approach for tendon repair. Statement of Significance: The poor healing capacity of injured tendons and inevitable peritendinous adhesion has made tendon regeneration a clinical priority. In this study, an asymmetric chitosan scaffold was developed to encapsulate rat tendon stem/progenitor cells (TSPCs), which could induce higher levels of tenogenic specific genes and protein expression. Remarkably, the introduction of TSPCs into the asymmetric chitosan scaffold generated a synergistic effect on in vivo tendon regeneration and lead to better-aligned collagen fibers compared with asymmetric chitosan scaffold alone. This work can provide new guidelines for the structure and property design of cell-seeded scaffolds for tendon regeneration.